2022
DOI: 10.3390/ijms23169329
|View full text |Cite
|
Sign up to set email alerts
|

DNA and RNA Binding Proteins: From Motifs to Roles in Cancer

Abstract: DNA and RNA binding proteins (DRBPs) are a broad class of molecules that regulate numerous cellular processes across all living organisms, creating intricate dynamic multilevel networks to control nucleotide metabolism and gene expression. These interactions are highly regulated, and dysregulation contributes to the development of a variety of diseases, including cancer. An increasing number of proteins with DNA and/or RNA binding activities have been identified in recent years, and it is important to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 260 publications
(269 reference statements)
0
1
0
Order By: Relevance
“…The DNA binding proteins (DBPs), especially the transcription factors (TFs), can bind to specific DNA motif patterns and regulate cellular activities, including chromosome packaging ( 3 ), transcription ( 4 ), and the expression of unique proteins ( 5 ). Moreover, the DNA–DBP binding process can further influence the progression of multiple diseases, including cancer ( 6–8 ), autoimmune disease ( 9 ), cognitive degradation ( 10 ) and diabetes ( 11 ). Past studies have demonstrated that most DNA motifs have ordered sequence patterns corresponding to their DBPs ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA binding proteins (DBPs), especially the transcription factors (TFs), can bind to specific DNA motif patterns and regulate cellular activities, including chromosome packaging ( 3 ), transcription ( 4 ), and the expression of unique proteins ( 5 ). Moreover, the DNA–DBP binding process can further influence the progression of multiple diseases, including cancer ( 6–8 ), autoimmune disease ( 9 ), cognitive degradation ( 10 ) and diabetes ( 11 ). Past studies have demonstrated that most DNA motifs have ordered sequence patterns corresponding to their DBPs ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%